2013
DOI: 10.1093/humrep/det286
|View full text |Cite
|
Sign up to set email alerts
|

Shorter anogenital distance correlates with undescended testis: a detailed genital anthropometric analysis in human newborns

Abstract: The study strengthens the hypothesis of existence of MPW in humans. Shorter AGD in cryptorchid infants may reflect the effect of androgen disruption or deficiency during MPW. AGD may be a more reliable non-invasive marker of androgen action during MPW than SPL to predict reproductive outcomes in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
62
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 42 publications
8
62
1
Order By: Relevance
“…5,34,48,81,83,89,189,190886887758640187828480778,92 For example, recent observations from a New Zealand birth cohort showed that the prevalence of all three of these markers within boys with orchidopexy-confirmed cryptorchidism was approximately twice that observed among non-cryptorchid boys. 189 In addition, relative foetal growth restriction is also associated with cryptorchidism: Jensen et al 34 observed that a twin born with cryptorchidism was, on average, 136g lighter (95% CI 70–202) than a non-cryptorchid male twin.…”
Section: Gestational Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,34,48,81,83,89,189,190886887758640187828480778,92 For example, recent observations from a New Zealand birth cohort showed that the prevalence of all three of these markers within boys with orchidopexy-confirmed cryptorchidism was approximately twice that observed among non-cryptorchid boys. 189 In addition, relative foetal growth restriction is also associated with cryptorchidism: Jensen et al 34 observed that a twin born with cryptorchidism was, on average, 136g lighter (95% CI 70–202) than a non-cryptorchid male twin.…”
Section: Gestational Factorsmentioning
confidence: 99%
“…Birth measures (birth weight, gestational age, size for gestational age) 5,8,34,40,48,68,75,77,8084,8689,92,187,189,190 …”
mentioning
confidence: 99%
“…Hence, AGD could be measured at any postnatal age in rats and used to retrospectively decipher the level of fetal androgen exposure during the MPW (11,21). In human males, AGD shows similar male-female differences as in rats (11,(24)(25)(26), and lower AGD has been related to the occurrence of TDS disorders evident at birth (27)(28)(29)(30)(31)(32)(33) and, in a majority of studies, to lower sperm counts (34)(35)(36)(37) and hormone levels (38,39) in adult men, similar to rats (reviewed in ref. 11).…”
Section: Introductionmentioning
confidence: 99%
“…37 Risk factors in maternal behavior, such as continuous smoking, drinking, caffeine intake, and use of mild analgesics during pregnancy, also seem to have adverse effects on the development and descent of the testis in their offspring, [38][39][40][41][42] although these findings are still controversial. 10,12,13 AGS has since also been associated with adult semen quality. These different types of cryptorchidism may not share the same etiology.…”
Section: Etiologymentioning
confidence: 99%